L’alliance normando-tupi au xvie siècle : la célébration de Rouen - Beatriz Perrone-Moisés (Journal de la Société des Américanistes)
The Norman-Tupi alliance in the 16th century: the celebration at Rouen.In 1550, the city of Rouen prepares a series of festivities for the royal entry of Henry II and his court, of which two elements point to the links between the Norman harbour merchants and the Brazilian coastal Tupi: a performance of the Indians’ daily life – called « Brazilian festival » by the historian Ferdinand Denis, involving 50 Tupi and 250 Norman sailors – and a staged naval battle between French and Portuguese. This article proposes to consider these festivities not so much as a display of exoticism or an anecdotal curiosity, but rather as a statement and celebration of alliances between the Normans and the Tupi, on which depend the success of the city’s transatlantic trade and, through the characteristic traits of these relations, the foundation of the wealth of the city and the quality of the performance. It also briefly considers some elements of the illustration of this performance, comparing it with the Tupi iconography of the same epoch.